(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2019)
We have presented a very simple, fast, general and efficient method for synthesis of 2,4,5- triarylimidazole derivatives via condensation of aldehydes, benzil/benzoin and ammonium acetate in the presence of In/AlMCM-41. All the synthesized compounds have been characterized on the basis of elemental analysis, IR, 1H NMR, and 13C NMR spectral studies.